2022
DOI: 10.3390/ijms23126397
|View full text |Cite
|
Sign up to set email alerts
|

Allethrin Promotes Apoptosis and Autophagy Associated with the Oxidative Stress-Related PI3K/AKT/mTOR Signaling Pathway in Developing Rat Ovaries

Abstract: The increased concern regarding the reduction in female fertility and the impressive numbers of women undergoing fertility treatment support the existence of environmental factors beyond inappropriate programming of developing ovaries. Among these factors are pyrethroids, which are currently some of the most commonly used pesticides worldwide. The present study was performed to investigate the developmental effects of the pyrethroid-based insecticide allethrin on ovarian function in rat offspring in adulthood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 63 publications
7
12
0
Order By: Relevance
“…Apoptosis in ovarian cells can cause extensive follicular atresia or regression and is considered to be one of the most important mechanisms underlying ovarian aging [19]. OS has been shown to induce apoptosis in ovarian cells by various processes, including exogenous pathways, endogenous pathways and by endoplasmic reticulum stress (ERS) [20][21][22]. In the exogenous pathway, excess ROS in ovarian tissue can activate the Fas/ FasL pathway and recruit caspase-8 (CASP8) to form a death-inducing signaling complex (DISC) with Fas and FasL.…”
Section: Apoptosismentioning
confidence: 99%
“…Apoptosis in ovarian cells can cause extensive follicular atresia or regression and is considered to be one of the most important mechanisms underlying ovarian aging [19]. OS has been shown to induce apoptosis in ovarian cells by various processes, including exogenous pathways, endogenous pathways and by endoplasmic reticulum stress (ERS) [20][21][22]. In the exogenous pathway, excess ROS in ovarian tissue can activate the Fas/ FasL pathway and recruit caspase-8 (CASP8) to form a death-inducing signaling complex (DISC) with Fas and FasL.…”
Section: Apoptosismentioning
confidence: 99%
“…Jalouli et al stressed the adverse effect of pyrethroid-based insecticides in developing rat ovaries [4]. Allethrin is one of the most commonly utilized pyrethroids.…”
mentioning
confidence: 99%
“…Autophagy plays a significant role in λ‐Cyhalothrin toxicity. According to a previous study, pesticides cause autophagy by increasing LC3B expression 78 . In another research, it was shown that the ratio of LC3B II/LC3B I reduced after 0.25 mM of pesticide was administered to N2a cells, but increased significantly while 1 mM of pesticide was administered.…”
Section: Discussionmentioning
confidence: 86%
“…According to a previous study, pesticides cause autophagy by increasing LC3B expression. 78 In another research, it was shown that the ratio of LC3B II/LC3B I reduced after 0.25 mM of pesticide was administered to N2a cells, but increased significantly while 1 mM of pesticide was administered. Their findings indicate that the impact of pesticides on autophagy varies with treatment dosage.…”
Section: Discussionmentioning
confidence: 95%